611 Oesophageal Atresia and Associated Anomalies. (October 2012) - Desai, P; Morris, J; Segal, L
Abstract : Background: In previous studies the incidence of associated congenital anomalies for infants with oesophageal atresia(OA) ranges between 40–57%. OA mostly associated with Tracheoesophageal fistula is a part of VACTERL association (V ertebral anomalies, A nal atresia, C ardiovascular anomalies, T racheoesophageal fistula, R enal/or radial anomalies, L imb defects). Aim: To determine the incidence of associated anomalies in babies with oesophageal atresia. Methods: 32 babies treated for oesophageal atresia at our regional surgical neonatal unit between the period February 2007 to February 2012 were included in the study. Results: Out of 32 babies, 17 were male and 15 were female infants with gestation ranging from 31–40 weeks. 10 babies (31%) were born in-utero and 22 babies were transferred from local neonatal units. Birth weights ranged between 1380g–4300g. In total 15 babies (47%) had some form of Cardiac anomalies with 5 babies either having Atrial septal defect or Ventricular septal defect and 8 babies having a patent ductus arteriosus (PDA). 3 babies (9%) had associated anorectal anomalies. In total 10 babies (31%) had associated anomaly excluding isolated PDA and 16 babies (50%) if isolated PDA were included. Conlcusion: Association of anomalies with Oesophageal anomalies is well documented in literature. It is important to identify vertebral anomalies early for follow up as the risk of scoliosis is 13 fold after repair of OA in relation to general population. This small study showed incidence of 50% for babies with OA to be associated with other anomalies and supports current literature.